Vitamin D Modulates the Expression of Toll-like Receptors and Pro-inflammatory Cytokines without Affecting Chikungunya Virus Replication, in Monocytes and Macrophages (2022)
ABSTRACT: Chikungunya virus (CHIKV) is a zoonotic arthropod-borne virus that causes Chikungunya fever (CHIKF), a selflimiting disease characterized by myalgia and acute or chronic arthralgia. CHIKF pathogenesis has an important immunological component since higher levels of pro-inflammatory factors, including cytokines and chemokines, are detected in CHIKV-infected patients. In vitro studies, using monocytes and macrophages have shown that CHIKV infection promotes elevated production of pro-inflammatory cytokines and antiviral response factors. Vitamin D3 (VD3) has been described as an important modulator of immune response and as an antiviral factor for several viruses. Here, we aimed to study the effects of VD3 treatment on viral replication and proinflammatory response in CHIKV-infected human monocytes (VD3-Mon) and monocyte-derived macrophages differentiated in the absence (MDMs) or the presence of VD3 (VD3-MDMs). We found that VD3 treatment did not suppress CHIKV replication in either VD3-Mon or VD3-MDMs. However, the expression of VDR, CAMP and CYP24A1 mRNAs was altered by CHIKV infection. Furthermore, VD3 treatment alters TLRs mRNA expression and production of pro-inflammatory cytokines, including TNFα and CXCL8/IL8, but not IL1β and IL6, in response to CHIKV infection in both VD3-Mon and VD3-MDMs. While a significant decrease in CXCL8/IL8 production was observed in CHIKV-infected VD3-Mon, significantly higher production of CXCL8/IL8 was observed in CHIKVinfected VD3-MDM at 24 hpi. Altogether, our results suggest that vitamin D3 may play an important role in ameliorating pro-inflammatory response during CHIKV infection in human Mon, but not in MDMs. Although further studies are needed to evaluate the efficacy of VD3; nevertheless, this study provides novel insights into its benefits in modulating the inflammatory response elicited by CHIKV infection in humans.